OPTIMALISASI ARSITEKTURAL BANGUNAN PAVILIUN BARU GUNA MENDUKUNG KEGIATAN TARUNA AKMIL - M. Hendro Kesuma; Agung Prapsetyo; M. Zain Triputra; Budi Mawardi Syam (PPM Sdirjianbang Akademi Militer, 2023)
The military academy is an educational institution in the Indonesian Army that produces officers with the rank of second lieutenant with a dormitory education system. Residential facilities are needed for education at the Military Academy. Cadets Level IV/Sermatutar occupy the Pavilion in undergoing Education. Of course, good architecture is needed so that cadets can carry out education comfortably. There is a comfort factor which is the architectural benchmark for the Pavilion which has indicators namely circulation, noise, aroma, safety, and cleanliness. Things must be in good condition to support Taruna's comfort in resting. The purpose of this research is to find out the optimization of the new pavilion to support comfort in the activities of Cadets of the Military Academy. This study uses a qualitative method. Primary data sources used observations in the form of documentation at the research location, results of interviews with Kazi Akmil, Lt. Col. Czi Noor Arif Khusaini, Sergeant Ally and samples of pavilion occupants namely Sermatutar Satrio, Sermatutar Dicky, and Sermatutar Qadri. While secondary data comes from literature and journals that support the completion of this Final Project. The results of this study are that the Architectural conditions of the Pavilion are quite good and make the cadets living in the Pavilion comfortable in carrying out their education. This is supported by the intention of the Engineers to be involved in renovating the pavilion with an architectural design that can support the comfort of cadets in carrying out activities in the pavilion.